Peningkatan Kompetensi Pengelolaan Jurnal Ilmiah Bagi Mahasiswa IBI Kesatuan Bogor - Munawar, Aang; Nurendah, Yulia; Mulyana, Mumuh; Rustandi, Imelda Elia; Suratman, Siti Azzahra; Apsari, Zahra Cikal Wahyu Apsari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital-based scientific journal management is a crucial element in strengthening academic culture and improving the quality of higher education publications. However, student involvement in journal governance remains limited, particularly in understanding editorial workflows, using Open Journal Systems (OJS), applying publication ethics, and utilizing supporting technologies such as reference management tools and editorial artificial intelligence (AI). This community service program aims to enhance students’ competencies in scientific journal management at the Institut Bisnis dan Informatika (IBI) Kesatuan Bogor through practice-oriented training and mentoring. The program employed an experiential learning and capacity-building approach, including OJS 3 technical workshops, editorial process simulations, focus group discussions (FGDs), and competency evaluations using pre-tests and post-tests. Participants consisted of students from various study programs with an interest in academic writing and scholarly publishing. The evaluation results indicate a significant improvement in participants’ competencies, with average scores increasing from 52.3% before the program to 86.7% after its implementation. The most substantial improvements were observed in OJS mastery, understanding of publication ethics, and the use of AI-based tools for proofreading and plagiarism detection. Furthermore, 82.5% of participants expressed readiness to serve as assistant editors for institutional journals, and 87.5% demonstrated increased motivation to write and publish scientific articles. This program contributes to strengthening students’ academic literacy, enhancing institutional journal management capacity, and supporting the implementation of Outcome-Based Education (OBE), the Merdeka Belajar Kampus Merdeka (MBKM) policy, and the achievement of higher education Key Performance Indicators (KPIs). Keywords: community service; scientific journal management; OJS; academic literacy; students; scholarly publishing.